Towards a flexible and generalizable computational model-based framework for mitigation of spatial disorientation in sensory-deprived environments. Issue 4 (December 2022) - Dixon, J.B.; Clark, T.K.; Endsley, T.
Abstract: Purpose: Spatial disorientation (SD), an incorrect perception of one's orientation, position or motion, jeopardizes the safety and performance of aviators, astronauts, and professionals in other domains such as SCUBA and firefighting. Active countermeasures can assist navigators in real-time with maintaining orientation – and may mitigate the deleterious impacts of SD. A necessary component of such a system, however, is a method by which to estimate possible SD being experienced, and detect when intervention is warranted. Computational tools utilizing models of human spatial orientation perception provides an unobtrusive means to estimate the spatial awareness of the navigator. Previously proposed computational detection methods, however, have been designed to capture specific SD events that are commonly experienced by fixed-wing aircraft pilots. We propose a generalizable computational framework that can be adapted to different environments, vehicles (e.g., spacecraft) and operating theatres. Proposal: We leverage the state-of-the-art Observer model to compute spatial orientation perception in sequence with an integrative algorithm to capture the severity of orientation misperception over time. A Bayesian likelihood model is used for system and parameter identification of the proposed algorithm candidates we have developed. A novel two-part experimental methodology is proposed to first gather necessary data for informing likelihood estimators (e.g., estimates of SD), and then assess the potential system benefits (e.g., safety, control performance) while using a well-tuned computational detection tool in real-time. Implementation: Simulated motion stimuli were used in the development of algorithm candidates and optimization techniques. Our simulation results and application of the generalized framework to various navigation environments demonstrate the utility of capturing all state parameters related to orientation perception (e.g., acceleration, angular velocity, zenith etc.) which enables the system to capture the continuum of SD involving a variety of different stimuli. As a proof-of-concept effort, we have developed an experimental paradigm representing a helicopter piloting scenario in the presence of mission-related distractions. Conclusion: The proposed computational tool, when appropriately fitted for the environment of relevance, may be used to trigger real-time countermeasure interventions for the goal of mitigating adverse impacts of SD events in operational environments. SD can manifest in drastically different ways given the sensory environment, such as an absence of a tonic loading of gravity during spaceflight. The integrative and generalizable nature of this framework may facilitate translatable progress in SD mitigation research across the many domains which it plagues.